The effects of 3-month skill-based and plyometric conditioning on fitness parameters in junior female volleyball players - Idrizovic, K.; Gjinovci, B.; Sekulic, D.; Uljevic, O.; Vicente João, P.; Spasic, M.; Sattler, T. (Pediatric Exercise Science, 2018)
Purpose: This study compared the effects of skill-based and plyometric conditioning (both performed in addition to regular volleyball training twice a week for 12 wk) on fitness parameters in female junior volleyball players. Methods: The participants [n=47; age: 16.6 (0.6) y; mass: 59.4 (8.1) kg; height: 175.1 (3.0) cm] were randomized into a plyometric (n=13), a skill-based (n=17), and a control (n=17) groups. The variables included body height, body mass, calf girth, calf skinfold, corrected calf girth, countermovement jump, 20-m-sprint, medicine ball toss, and sit-and-reach test. Results: Two-way analysis of variance (time×group) effects for time were significant (P<.05) for all variables except body mass. Significant group×time interactions were observed for calf skinfold [2=.14; medium effect size (ES)], 20-m sprint (2=.09; small ES), countermovement jump (2=.29; large ES), medicine ball (2=.58; large ES), with greater gains (reduction of skinfold) for plyometric group, and sit-and-reach (2=.35; large ES), with greater gains in plyometric and skill-based groups. The magnitude-based inference indicated positive changes in 1) medicine ball toss and countermovement jump for all groups; 2) sit-and-reach for the plyometric and skill-based groups; and 3) 20-m sprint, calf girth, calf skinfold, and corrected calf girth for plyometric group only. Conclusion: Selected variables can be improved by adding 2 plyometric training sessions throughout the period of 12 weeks. Additional skill-based conditioning did not contribute to improvement in the studied variables compared with regular volleyball training.